Transcriptome Analysis of Multiple Metabolic Tissues in High-Salt Diet–Fed Mice - Mao, Fei; Wang, E.; Xu, Jing; Lu, Jin; Yan, Guofeng; Fu, Li; Jiao, Yang; Wu, Ling; Liu, Tiemin; Li, Yao (Frontiers in Endocrinology, 2022)
High salt diet (HSD) is associated with dysregulated metabolism and metabolic disorders. Although previous studies have indicated its effect on metabolic tissues, the involving molecular mechanisms are not quite understood. In the present study, we provided a comprehensive transcriptome analysis on multiple metabolic tissues of high salt diet-fed mouse model by RNA sequencing. We observed that several genes associated with de novo lipogenesis and cholesterol biosynthesis were significantly down-regulated in WAT and liver tissue of HSD mice group, such as Fasn, Scd1, Acaca, Thrsp. Besides, combined with secretome datasets, our results further demonstrated that HSD could alter expression levels of organokines in metabolic tissues, for example, TSK, Manf in liver tissue, and thus, possibly mediate crosstalk between different metabolic tissues. Our study provided new insight about molecular signatures of high-salt diet on multiple metabolic tissues.